Effect of Using Chicken Manure, Starfruit Waste, and Ice Cream Waste As Food Media on the Production Performance of Maggot Black Soldier Fly - Anang WIDIGDYO; Rani Arifah NORMAWATI (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to determine the effect of the use of chicken manure, starfruit waste and ice cream waste as a food medium on the production performance of Maggot BSF. The method used in this study was experimental by applying a Complete Randomized Design. The results showed that the combined use of chicken manure waste and organic waste with treatment variations did not have a significant effect (P>0.05) on weight gain and the specific daily growth rate of BSF maggots. The highest weight gain results were obtained at P4 treatment of 622 grams and the lowest in P3 treatment of 560 grams. The specific daily growth rate of BSF maggots was highest in the P4 treatment at 11.22% and the lowest in the P3 treatment at 10.53%. The ability in this study was the use of a combination of chicken manure and ice cream waste with a ratio of 50% : 50% providing weight gain and a specific daily growth rate of Black Soldier Fly maggots.